Exploring the impact of 3D printing technology on patient-specific prosthodontic rehabilitation: A comparative study - Swati Kharat; Soumya Iranna Dudhani; Afreen Kouser; Ponniah Subramanian; Debarshi Bhattacharjee; Vikram Jhamb (Wolters Kluwer Medknow Publications, 2024)
Introduction: The rapid advancement of 3D printing technology has opened new avenues for patient-specific prosthodontic rehabilitation. This study aimed to explore the impact of 3D printing technology on prosthodontic outcomes and patient satisfaction through a comparative analysis. Materials and Methods: A total of 100 patients requiring prosthodontic rehabilitation were recruited for this study. The patients were randomly divided into two groups: the experimental group, where 3D printing technology was utilized for the fabrication of patient-specific prostheses, and the control group, where conventional fabrication techniques were employed. Various parameters were assessed, including prosthesis fit, occlusion, esthetics, and patient-reported outcomes such as comfort and satisfaction. Digital measurements and subjective evaluations were conducted to compare the outcomes between the two groups. Statistical analysis was performed using appropriate tests. Results: Preliminary findings indicated that the use of 3D printing technology in prosthodontic rehabilitation resulted in superior prosthesis fit, enhanced occlusal stability, and improved esthetics compared to conventional methods. Moreover, patients in the experimental group reported higher levels of comfort and overall satisfaction. The advantages of 3D printing technology were observed across different types of prosthodontic restorations, including crowns, bridges, and dentures. These results highlight the potential of 3D printing technology to revolutionize patient-specific prosthodontic rehabilitation. By facilitating precise fabrication, customization, and improved functional outcomes, 3D printing can enhance the overall quality of prosthodontic care. Further long-term studies are warranted to validate these findings and explore the cost-effectiveness and long-term durability of 3D-printed prostheses. Conclusion: In conclusion, this study demonstrates that the integration of 3D printing technology in patient-specific prosthodontic rehabilitation holds great promise for achieving optimal functional and esthetic outcomes. The findings contribute to advancing prosthodontic practices and provide valuable insights for clinicians and researchers seeking to incorporate this innovative technology into their treatment protocols.